Catalisadores heterogêneos aplicados à reação de Biginelli - Nascimento, Letícia Gomes do (2017)
The Biginelli reaction involves the cyclocondensation of three reagents in the presence of an acid catalyst to obtain dihydropyrimidinones (DHPMs).This compound and its analogues are widely known to possess various pharmacological properties, such as antibacterial, antiinflammatory, antifungal, antiviral, anticancer and antihypertensive. This reaction is usually carried out via homogeneous catalysis, which presents, however, some difficulties, such as regeneration of the catalyst and difficult separation of the final product, thus becoming an obstacle for industrial use. In the present work, it was proposed the use of two classes of heterogeneous catalysts, which are: metal oxides and acid carbons in order to achieve attractive characteristics in the Biginelli reaction, as a reduction of reaction time and increase in yield. The acidic carbons were prepared by carbonization by impregnation of agroindustrial residues with sulfuric acid at a temperature of 200 °C in the mass ratio of 1:10 (precursor: H2SO4) for 6 h. The pure HY-340 and Nb2O5 were both tested and chemically treated with a solution of 30% sulfuric acid. The catalysts were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR), thermogravimetric (TG), differential thermal analysis (DTA), textural adsorption/desorption analysis of N2 at -196 °C and desorption of ammonia at programmed temperature (DTP-NH3), scanning electron microscopy (SEM) and X-ray Dispersive Energy Spectrometry (EDS). The contents of C, N, O and S present on the surface of the coals were quantified by Elementary Analysis (CHNS-O). Exploratory catalytic tests were carried out to define the best experimental conditions of solvent, temperature, molar ratio and amount of catalyst. The results obtained allowed to establish the best experimental conditions for the realization of the Biginelli reaction. Thus, the following parameters were adopted to evaluate the performance of the different catalysts. These are: 5% catalyst content (by mass), molar ratio of 1 Benzaldehyde: 1,5 Methyl acetoacetate: 1,5 Urea, without solvent and temperature of 130 °C. The best catalyst was Nb2O5 treated with sulfuric acid, whereby a yield of 94% of dihydropyrimidinones (DHPMs).